PROGRAM-TARGET METHOD OF PLANNING OF THE COST OF CONDUCTING EXERCISES - Z. Uvarova; G. Bashashkina (Вестник университета)
The article highlights the possibility of using program-target method of planning of expenses for combat training of troops (forces), reflects the stages of applications of program planning, given the calculation formula and the main stages of forecasting the costs of the conduct of the exercise